GLP-2 Prevents Intestinal Mucosal Atrophy and Improves Tissue Antioxidant Capacity in a Mouse Model of Total Parenteral Nutrition - Qiucheng Lei (Nutrients, 2016)
We investigated the effects of exogenous glucagon-like peptide-2 (GLP-2) on mucosal atrophy and intestinal antioxidant capacity in a mouse model of total parenteral nutrition (TPN). Male mice (6–8 weeks old) were divided into three groups (n = 8 for each group): a control group fed a standard laboratory chow diet, and experimental TPN (received standard TPN solution) and TPN + GLP-2 groups (received TPN supplemented with 60 µg/day of GLP-2 for 5 days). Mice in the TPN group had lower body weight and reduced intestinal length, villus height, and crypt depth compared to the control group (all p < 0.05). GLP-2 supplementation increased all parameters compared to TPN only (all p < 0.05). Intestinal total superoxide dismutase activity and reduced-glutathione level in the TPN + GLP-2 group were also higher relative to the TPN group (all p < 0.05). GLP-2 administration significantly upregulated proliferating cell nuclear antigen expression and increased glucose-regulated protein (GRP78) abundance. Compared with the control and TPN + GLP-2 groups, intestinal cleaved caspase-3 was increased in the TPN group (all p < 0.05). This study shows GLP-2 reduces TPN-associated intestinal atrophy and improves tissue antioxidant capacity. This effect may be dependent on enhanced epithelial cell proliferation, reduced apoptosis, and upregulated GRP78 expression.